Elevated Positive End-Expiratory Pressure Decreases Cardiac Index in a Rhesus Monkey Model - Ross, Patrick A.; Khemani, Robinder G.; Rubin, Sarah S.; Bhalla, Anoopindar K.; Newth, Christopher J. L. (Frontiers in Pediatrics, 2014)
Rationale: Clinicians are often concerned that higher positive end expiratory pressure (PEEP) will decrease cardiac index (CI). PEEP affects cardiac index through multiple inter-related mechanisms. The adult Rhesus monkey is an excellent model to study cardiopulmonary interaction due to similar pulmonary and chest wall compliances to human infants. Objective: Our goal was to examine the impact of increasing PEEP on cardiac index in Rhesus monkeys as a model for critically ill children. Methods: Prospective, experimental animal study. Nine healthy anesthetized, intubated Rhesus monkeys were allowed to breathe spontaneously at a PEEP of 0, 5, 10, and 15 cm H2O while cardiac index was measured with an ultrasonic Doppler (USCOM). Measurements and Main Results: Cardiac index decreased between PEEP levels of 5 cm H2O and 15 cm H2O. The mean decrease in CI for the entire cohort of monkeys was 18% (p<0.01) with a range of -11 to 49%. Stroke volume and oxygen delivery also decreased between PEEP levels of 5 cm H2O and 15 cm H2O (p<0.01). Conclusions: Between PEEP levels of 5 cm H2O and 15 cm H2O there was a decrease in cardiac index, stroke volume, and oxygen delivery in intubated Rhesus monkeys. A plausible mechanism is that over-distention of normally compliant lungs at increased PEEP resulted in decreased preload to the right ventricle, outweighing the potentially beneficial decrease in left ventricular afterload or pulmonary vascular resistance. Further investigation is warranted, particularly in children with lung injury, who have historically benefitted from increased PEEP levels without over-distention.